2011
DOI: 10.1001/jama.2010.2008
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Florbetapir-PET for Imaging β-Amyloid Pathology

Abstract: ment of Alzheimer disease (AD) are hampered by the lack of noninvasive biomarkers of the underlying pathology. Between 10% and 20% of patients clinically diagnosed with AD lack AD pathology at autopsy, 1-3 and community physicians may not diagnose AD in 33% of patients with mild signs and symptoms. 4 Thus, a diagnostic biomarker may help clinicians separate patients who have AD pathology from those who do not. See also pp 261 and 304.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
814
1
22

Year Published

2011
2011
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 985 publications
(863 citation statements)
references
References 35 publications
26
814
1
22
Order By: Relevance
“…There are four PET imaging agents that have been well-studied in humans: [ 11 C]PIB, 2 florbetapir f18 (Amyvid), 3,4 florbetaben f18, 5 and flutemetamol f18 6 (Figure 2A). Results of a phase 3 Figure 2B).…”
Section: ■ Aβ Plaque-specific Imaging For Diagnosis and Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four PET imaging agents that have been well-studied in humans: [ 11 C]PIB, 2 florbetapir f18 (Amyvid), 3,4 florbetaben f18, 5 and flutemetamol f18 6 (Figure 2A). Results of a phase 3 Figure 2B).…”
Section: ■ Aβ Plaque-specific Imaging For Diagnosis and Drug Developmentmentioning
confidence: 99%
“…Results of a phase 3 Figure 2B). 3 It is now pending FDA approval for routine clinical uses. The development of diagnostic imaging agents targeting Aβ aggregates may lead to improved selection and monitoring of patients undergoing drug treatment designed to reverse the Aβ plaque buildup in the brain.…”
Section: ■ Aβ Plaque-specific Imaging For Diagnosis and Drug Developmentmentioning
confidence: 99%
“…In area 9 of the frontal cortex-a region demonstrating remarkably high uptake of amyloid radiotracers-the percentage of total area occupied by amyloid plaques was shown by one histopathological study to be approximately 7.11% in AD patients [38]. Similarly, the histopathological component of the phase III florbetapir study found that the average amyloid burden in the precuneus, another region of high uptake, was 5.24% in nine patients for whom AD was named as the cause of death [7]. If it is assumed that amyloid burden in end-stage AD constitutes roughly 6% (in terms of area fraction) of the most severely affected cortical regions, and that the contrast between plaque and background must be at least twofold in order to visualize these structures with PET, the differential uptake of these amyloid tracers must be at least 100 times greater in amyloid plaques than in the background (Appendix; Fig.…”
Section: Difficulties In Visualizing Amyloid Plaquesmentioning
confidence: 98%
“…However, the advent of three new radiotracers, which are currently at various stages of FDA assessment and approval, has brought amyloid imaging to the doorstep of clinical use. Recent clinical studies on florbetapir (AV-45), florbetaben (BAY-94), and flutemetamol (GE-067) claim to have demonstrated an ability to discriminate between AD patients and healthy controls with high degrees of sensitivity and specificity [6][7][8][9][10][11]. However, the theoretical bases of and ubiquitous patterns in the reported data raise a host of lingering questions that should be addressed before these radiotracers are clinically approved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation